Mechanisms of Action of Toxins Released by Clostridium perfringens - Raza, Ali; Sumaira Goshi; Khan, Ali; Mahmood, Saher; Goshi, Sumaira; Khalid, Rmisha; Ijaz, Minahil; Shaheen, Muqaddas; Noor, Aqsa; Bano, Shaher; Asghar, Sabahat; Afzal, Tania; et al. (BioScientific Review, 2024)
Clostridium perfringens, a rod-shaped anaerobe, is a Gram-positive bacterium that causes foodborne diseases. Its generation time is less than ten minutes and it can divide at 45°C. This aerotolerant bacterium has some toxigenic types (A, B, C, D, and E) that can cause diseases in human beings. Two of its newly discovered toxin types are F and G. Histotoxic, neurological, and intestinal illnesses in both people and animals are instigated by C. perfringens due to its wide range of protein toxins. Alpha or CPA, beta or CPB, epsilon or ETX, iota or ITX, and enterotoxin or CPE are the primary toxins that contribute toward diseases. CPA is the primary pathogenicity factor in gas poisoning in human beings, despite its limited and debatable involvement in animal illnesses. Necrotizing intestinal inflammation and enterotoxaemia in infants of various vertebrate species, particularly humans, are caused by CPB. Some other types cause illnesses in livestock. Necrotic and apoptotic traits are present in the molecular pathways of cell damage linked to C. perfringens toxins.